Neutrophil Elastase Subverts the Immune Response by Cleaving Toll-Like Receptors and Cytokines in Pneumococcal Pneumonia - Domon, Hisanori; Nagai, Kosuke; Maekawa, Tomoki; Oda, Masataka; Yonezawa, Daisuke; Takeda, Wataru; Hiyoshi, Takumi; Tamura, Hikaru; Yamaguchi, Masaya; Kawabata, Shigetada; Terao, Yutaka (Frontiers in Immunology, 2018)
Excessive activation of neutrophils results in the release of neutrophil elastase, which leads to lung injury in severe pneumonia. Previously, we demonstrated a novel immune subversion mechanism involving microbial exploitation of this neutrophil elastase ability, which eventually promotes disruption of the pulmonary epithelial barrier. In the present study, we investigated the effect of neutrophil elastase on host innate immune response. THP-1-derived macrophages were stimulated with heat-killed Streptococcus pneumoniae or lipopolysaccharide in the presence or absence of neutrophil elastase followed by analysis of toll-like receptor and cytokine expression. Additionally, the biological significance of neutrophil elastase was confirmed in an in vivo mouse intratracheal infection model. Neutrophil elastase down-regulated the gene transcription of multiple cytokines in THP-1-derived macrophages through the cleavage of toll-like receptors and myeloid differentiation factor 2. Additionally, neutrophil elastase cleaved inflammatory cytokines and chemokines. In a mouse model of intratracheal pneumococcal challenge, administration of a neutrophil elastase inhibitor significantly increased proinflammatory cytokine levels in bronchoalveolar lavage fluid, enhanced bacterial clearance, and improved survival rates. Our work indicate that neutrophil elastase subverts the innate immune response and that inhibition of this enzyme may constitute a novel therapeutic option for the treatment of pneumococcal pneumonia.